A review on photodegradation of organic pollutants using spinel oxide. (December 2020) - Kirankumar, V.S.; Sumathi, S.
Abstract: Spinel oxide has produced rapid improvement in various applications such as catalysis, sensors, batteries, degradation of dyes, drug delivery, and so on. In the current age, most of the researches are engrossed on spinel oxides for their photocatalytic activity because proficient exclusion of organic contaminants from wastewater has become a hot research topic by considering the environment. Photocatalytic degradation of organic contaminants is advantageous over conventional wastewater treatment technique like desalination, adsorption, and reverse osmosis. The current review demonstrates the photocatalytic activity of aluminate, ferrite spinel oxides, and modified spinel oxide for the removal of organic pollutants. This article comprises the structure, process of synthesis of spinel oxide, properties, photocatalytic activity, and reaction mechanism of degradation. In the end, future research needed to enhance the photocatalytic activity is discussed. Graphical abstract: Image 1 Highlights: Synthetic techniques used for spinel oxide are discussed. Properties of spinel oxide based on size and morphology are reviewed. Photodegradation of various organic pollutants using spinel oxides are reviewed.